The glycoprotein G of rhabdoviruses - Coll, J M (Archives of virology, 1995)
Rhabdoviruses show an RNA-containing helically-wound nucleocapsid either enclosed by or enclosing a membrane M protein, surrounded by a lipid bilayer through which dynamic protein trimers made up of non-covalently associated monomers of glycoprotein G (G) project outside. Mature monomeric rhabdoviral G has more than 500 amino acids, 2-6 potential glycosylation sites, 12-16 highly conserved cysteine residues, 2-3 stretches of a-d hydrophobic heptad-repeats, a removed amino terminal hydrophobic signal peptide, a close to the carboxy terminal hydrophobic transmembrane sequence and a carboxy terminal short hydrophylic cytoplasmic domain. Association-dissociation between monomers-trimers and displacement of the trimers along the plane of the lipid membrane, are induced by changes in the external conditions (pH, temperature, detergents, etc.). Throughout conformational changes the G trimers are responsible for the virus attachment to cell receptors, for low-pH membrane fusion and for reacting with host neutralizing monoclonal antibodies (MAbs). Antigenic differences could exist between monomers and trimers, which may have implications for future vaccine developments. The family Rhabdoviridae is made up of the Lyssavirus (rabies), the Vesiculovirus (vesicular stomatitis virus, VSV) and many rhabdoviruses infecting fish, plants, and arthropod insects. All these reasons make the G of rhabdoviruses an ideal subject to study comparative virology and to investigate new vaccine technologies.